O Japão na Amazônia: condicionantes para a fixação e mobilidade dos imigrantes japoneses (1929-2009) - MUTO, Reiko (Universidade Federal do Pará, 2011)
This paper investigates the immigration of Japanese people in to the Northern Region of Brazil and the variables that lead to the establishment of agricultural colonies in the State of Pará. It analyses the mobility of agriculture colonies from other regions, with particular attention given to the Tome-Açu (Pará) and the Amapá colonies, where the former colony is considered a successful case and the latter, the opposite. To achieve this, the thesis addresses current immigration theory, the international migration context between Brazil and Japan and national context of Japanese immigration. On the local approach, it discusses questions related to negotiations between the Brazilian Government and Japanese immigration promoting companies that occurred in the Amazon, Pará and Amapá states; In addition the paper covers the public policies aimed at establishing immigrants before and after the Second World War and the difficulties of different Japanese colonies that established in the Northern Region. The research is based on the bibliographical information and interviews with Japanese immigrants. From the data analysis, it was concluded, the planned migration model established in previously selected places by the Japanese representatives on the present Tome-Açu city in the beginning of immigration (1920‘s) and the following investments of private Japanese companies, and of the Japanese Government after Second World War were determining to the establishment of the immigrants in Tome-Açu. On the directioned immigration model (post WWII) on the colonies of Amapá land proceeded without proper planning of agricultural planting and research, hindered the planting and transport of goods. In addition, the health of many immigrants was compromised by endemic diseases in the region. These factors contributed to exodus of the majority of immigrants who searched other alternatives for their survival.